Evaluación de la evapotranspiración de productos satelitales en la zona sur del ecuador, 1990-2013 - Cardenas Torres, Marco Andres (Machala : Universidad Técnica de Machala, 2021)
Over the years, the indiscriminate use of fresh water has diminished the planet's natural reserves and conventional agriculture is a participant in this abuse. In order to control this fact to some extent, calculations of water needs are used and the most popular method is the calculation of evapotranspiration (ETo), which allows controlling irrigation and conserving water for agriculture. The Hargreaves method allows estimating ETo, using air temperature and extraterrestrial radiation. In general, the Hargreaves equation is recommended for weekly calculations or even for much longer periods, although there have been cases in which very accurate daily ETo estimates have been found. Satellite images are obtained through numerous remote sensors, there is a sensor that is used very frequently which is MODIS, it allows estimating from various inputs such as: the type of soil cover, leaf area index, albedo, among others. The general objective of the research is to evaluate the evapotranspiration of satellite products in the southern zone of Ecuador, period 1990-2013, using Hargreaves (HG) as a reference for the estimation of correlation and efficiency of remote sensing information. The research included the study of 15 meteorological stations for ETo determination by means of Hargreaves and MODIS, which are located in the southern part of Ecuador. Geographically, it is located between the parallels of 3º and 5º south latitude and the meridians of 78º and 81º west longitude. The southern zone of Ecuador includes the Jambelí Archipelago, the coastal zone of the province of El Oro, the highlands passing through the province of Loja and the Amazonian part belonging to the province of Zamora Chinchipe. Information was taken from the yearbooks of the official website of INAMHI (National Institute of Meteorology and Hydrology), the monthly scale data were digitized in the time series from 1990 to 2013, where variables of maximum and minimum temperature were considered, from which the average temperature was derived as a necessary variable for the calculation of evapotranspiration. Data extraction was performed using MODISTools, NDVI and EVI were downloaded at 500m2 resolution and with a good pixel reliability to allow quality control before analysis. The Hargreaves (HG) equation was used to calculate ETo, a method based on the use of temperature and solar radiation. The exploratory analysis of the climatic elements of the meteorological stations was carried out through a study where 15 stations were analyzed, 4 of which are located in the province of El Oro, 10 in the province of Loja and the remaining one in the province of Zamora Chinchipe. This was achieved through the description of graphics generated in ArcMap where a dividing line is denoted which corresponds to the Andean zone of Ecuador, which is above 1000 meters above sea level where 62.5% of the stations are distributed in this territory. Potential evapotranspiration was estimated by Hargreaves on an annual basis where scatter plots were grouped by provinces for a better understanding of the behavior of ETo values over the years, where there were significant fluctuations and gaps in values. The correlation between ETo from the Hargreaves equation and MODIS showed a weak positive Pearson correlation coefficient with a value of 0.31, the p-value of the analysis of variance is 0.001; consequently, there is a significant relationship between the variables with a confidence level of 95%. Furthermore, the coefficient of determination or goodness of fit only explains 10 of the variability between HG and MODIS, implying a weak relationship between the variables. The RMSE value indicates that the standard deviation of ETo is 1.01 mm/day, also a Bias or underestimated bias of -11.52 is obtained.
En el transcurso de los años, el uso indiscriminado del agua dulce ha disminuido las reservas naturales del planeta y la agricultura convencional es partícipe de ese abuso, para poder controlar en cierta parte este hecho, se utiliza los cálculos de las necesidades hídricas y con ello el método más popular es el cálculo de evapotranspiración (ETo) que permite controlar el riego y conservar el agua para la agricultura. El método de Hargreaves permite estimar la ETo, utiliza la temperatura del aire y la radiación extraterrestre. En general la ecuación de Hargreaves se recomienda para cálculos semanales o incluso que abarquen periodos mucho más largos, aunque se han dado casos en las que se encuentra estimaciones diarias de ETo muy precisas. Las imágenes satelitales se obtienen a través de numerosos sensores remotos, existe un sensor que se utiliza con mucha frecuencia que ese el de MODIS, permite estimar a partir de diversos insumos tales como: el tipo de cobertura del suelo, índice de área foliar, albedo, entre otros. La investigación tiene como objetivo general: evaluar la evapotranspiración de productos satelitales en la zona sur del Ecuador, periodo 1990-2013, usando como referencia Hargreaves (HG) para la estimación de la correlación y eficiencia de la información de sensoramiento remoto. La investigación abarco el estudio de 15 estaciones meteorológicas para la determinación de ETo por medio de Hargreaves y MODIS, las mismas que se encuentran en la zona sur del Ecuador. Geográficamente se encuentra localizada entre los paralelos de 3º y 5º de latitud sur y los meridianos de 78º y 81º de longitud oeste. La zona sur del Ecuador, comprende el Archipiélago de Jambelí, la zona costera de la provincia de El Oro, pasa por la Sierra pasando por la provincia de Loja y tiene parte amazónico perteneciente a la provincia de Zamora Chinchipe. Se tomo información de los anuarios de la página oficial del INAMHI (Instituto Nacional de Meteorología e Hidrología), los datos a escala mensual se digitalizaron en la serie temporal del año de 1990 a 2013, donde se consideraron variables de temperatura máxima y mínima, de la cual se derivó la temperatura promedio que parte como variable necesaria para realizar el cálculo de evapotranspiración. La extracción de datos se la realizo mediante MODISTools, se descargó NDVI y EVI a 500m2 de resolución y con una buena fiabilidad de píxeles para permitir el control de calidad antes del análisis. Para el cálculo de ETo se utilizó la ecuación de Hargreaves (HG), método que se basa en el uso temperatura y de la Radiación solar. El análisis exploratorio de los elementos climáticos de las estaciones meteorológicas se lo realizo mediante un estudio donde se analizaron 15 estaciones de las cuales 4 se encuentran en la provincia de El Oro, 10 en la provincia de Loja y la restante en la provincia de Zamora Chinchipe, se logró mediante la descripción de gráficos generados en ArcMap donde se denota una línea divisora la cual corresponde a la zona andina del Ecuador, el cual está por arriba de los 1000 msnm donde el 62.5% de las estaciones están distribuidas en este territorio. Se estimo la evapotranspiración potencial mediante Hargreaves de forma anual donde se agruparon los gráficos de dispersión por provincias para un mejor entendimiento del comportamiento de los valores de ETo en el transcurso de los años, donde se presentaron notables fluctuaciones y vacíos de valores. Se mostro la correlación existente entre la ETo de la ecuación de Hargreaves y MODIS, se presenta un coeficiente de correlación de Pearson positivo débil con un valor de 0.31, el p-valor del análisis de varianza es de 0.001; en consecuencia, hay una relación significativa entre las variables con un nivel de confianza del 95%. Además, que el coeficiente de determinación o bondad de ajuste solo explica el 10 de la variabilidad entre HG y MODIS, dando a entender una relación débil entre las variables. El valor de RMSE indica que la desviación estándar de la ETo es de 1.01 mm/día, también se obtiene un Bias o sesgo subestimado de -11.52.
Keywords: EVAPOTRANSPIRACIÓN; HARGREAVES; MODIS; TEMPERATURA